ORGANIZATIONAL PEDAGOGICAL ACTIVITY AND TRAINING FUTURE TEACHERS TO EDUCATIONAL WORK IN SUMMER CHILDREN’S HEALTH CAMPS - Голоденко, О. М.; Голоденко, С. М.; Голоденко, М. М. (Pedagogy of Higher and Secondary Education, 2011)
The article highlights the organizational pedagogical activity in a summer camp for children.